PENGEMBANGAN PERANGKAT PEMBELAJARAN DENGAN PENERAPAN MODEL PROBLEM BASED LEARNING PADA MATERI UKURAN PEMUSATAN DAN PENYEBARAN DATA KELAS VIII - Ariska Arintika; Rini Dian Anggraini; Atma Murni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The background of this research is motivated by the limited number of mathematics learning devices that can be used as references by teachers in developing learning devices independently in accordance with the demands of the 2013 curiculum. The purpose of this study is to produce a learning devices with a problem based learning model on the material of the size concentration and dissemination of data Class VIII. Learning instruments in this study are syllabus, lesson plans, and student worksheet. The develoment model used is model 4D by define, design, develop, disseminate. The research instrument used was an instrument of validity and practicality. The validity instrument is a validation sheet to assess the validity and learning tools. Practicality instruments in the form of question naire responses of students to the use of LKPD. Based on the results of data analysis, it can be concluded that the mathematics learning tool is considered to be very valid with an average rating for the syllabus is 3.69, RPP is 3.62 and LKPD is 3.62. This LKPD has also fulfilled the practicality requirements with an score average student response questionnaire reaching 3.52 in large group trials.Key Words: Mathematics Learning Devices, Problem Based Learning, Researchand Development.